Mechanism of Remediation of Cadmium-Contaminated Soil With Low-Energy Plant Snapdragon - Zhi, Yang; Zhou, Qixing; Leng, Xue; Zhao, Chunlei (Frontiers in Chemistry, 2020)
In the process of remediation of contaminated soil, we should give full play to the role of low-energy plants and fully display the concept of modern energy-saving and environmental protection. Phytoremediation is an effective method to remediate cadmium-contaminated soil, and root exudates play an important role in this process. Here, the response of snapdragon in a pot-culture experiment under two concentrations of Cd (1.0 and 2.5 mg/kg) was evaluated. Snapdragon is a medicinal plant with low energy consumption, which has low requirements on environmental factors and strong resistance. Results showed that Cd at both concentrations interferes with the uptake of a number of micro-and macro-nutrients, such as B, P, Cu, Mn, Mo, and Zn. The results also showed that plant type and Cd stress can significantly change the concentrations and species of root exudates. The metabolic changes of root exudates revealed the active defense mechanism against Cd stress: up-regulating of amino acids to sequester/exclude Cd; regulation of citric acid on chelation/complexation and precipitation of cadmium ions. The application of snapdragon can effectively reduce energy consumption and gradually improve the utilization rate of vegetation, which promotes the degradation of cadmium pollutants in soil.